Spatio-Temporal Variability in White Shark (Carcharodon carcharias) Movement Ecology During Residency and Migration Phases in the Western North Atlantic - Franks, Bryan R.; Tyminski, John P.; Hussey, Nigel E.; Braun, Camrin D.; Newton, Alisa L.; Thorrold, Simon R.; Fischer, George C.; McBride, Brett; Hueter, Robert E. (Frontiers in Marine Science, 2021)
Understanding how mobile, marine predators use three-dimensional space over time is central to inform management and conservation actions. Combining tracking technologies can yield powerful datasets over multiple spatio-temporal scales to provide critical information for these purposes. For the white shark (Carcharodon carcharias), detailed movement and migration information over ontogeny, including inter- and intra-annual variation in timing of movement phases, is largely unknown in the western North Atlantic (WNA), a relatively understudied area for this species. To address this need, we tracked 48 large juvenile to adult white sharks between 2012 and 2020, using a combination of satellite-linked and acoustic telemetry. Overall, WNA white sharks showed repeatable and predictable patterns in horizontal movements, although there was variation in these movements related to sex and size. While most sharks undertook an annual migratory cycle with the majority of time spent over the continental shelf, some individuals, particularly adult females, made extensive forays into the open ocean as far east as beyond the Mid-Atlantic Ridge. Moreover, increased off-shelf use occurred with body size even though migration and residency phases were conserved. Summer residency areas included coastal Massachusetts and portions of Atlantic Canada, with individuals showing fidelity to specific regions over multiple years. An autumn/winter migration occurred with sharks moving rapidly south to overwintering residency areas in the southeastern US Atlantic and Gulf of Mexico, where they remained until the following spring/summer. While broad residency and migration periods were consistent, migratory timing varied among years and among individuals within years. White sharks monitored with pop-up satellite-linked archival tags made extensive use of the water column (0 – 872 m) and experienced a broad range of temperatures (-0.9 – 30.5° C), with evidence for differential vertical use based on migration and residency phases. Overall, results show dynamic inter- and intra-annual three-dimensional patterns of movements conserved within discrete phases. These results demonstrate the value of using multiple tag types to track long-term movements of large mobile species. Our findings expand knowledge of the movements and migration of the WNA white shark population and comprise critically important information to inform sound management strategies for the species.